Worsened Dysrhythmia after Chemical Cardioversion with Digoxin; a Case of Malpractice - Hashemi, Behrooz; Pishgahi, Mehdi; Maleki, Marzieh (Archives of Academic Emergency Medicine, 2014)
The patient was a 23-year-old man referred to the emergency department (ED) with the chief complaint of palpitation. The patient experienced dizziness, cold sweating, and lightheadedness after getting up which started spontaneously. He had four episodes of the same problems in seven months ago that felt better after taking 10 mg propranolol. But, in the current episode his problem was not solved by the same medication. He had no history of smoking, substance abuse, medication use, congenital heart disease, syncope, previous surgery, chest trauma, or any other known medical problems. As well, he had no any positive history of the same problems in his family. The patients’ on-arrival vital signs were as follow: systolic blood pressure (SBP): 90 mmHg, pulse rate (PR): 150/minute, respiratory rate (RR): 14/minute, oral temperature: 37◦C, oxygen saturation 96% with nasal cannula and 100% oxygen, Glasgow coma scale (GCS) 15/15. He was not experienced any other concomitant problems such as ischemic chest discomfort, shortness of breathing, or sign of circulatory shock such as paleness, mottling, etc. On general physical examination the patients’ lung and heart sounds, four limbs pulses, and capillary refile were normal. As well, focused neurological and abdominal examinations did not have any positive finding. The patient underwent close cardiac, vital sign monitoring and electrocardiography (ECG). Figure 1 shows the on-arrival patients’ ECG. Atrial fibrillation (AF) was diagnosed by the corresponding physician and digoxin (!?) prescribed that led to severe lethargy, weakness, sweating, and bradycardia. Figure 2 shows the post mediation ECG of patient.